Tree Risk Assessment Methods: A Comparison of Three Common Evaluation Forms - Andrew K. Koeser; Gitta Hasing; Drew McLean; Robert Northrop (EDIS)
All trees pose some level of risk to nearby people, structures, and utilities. As trees age or become weakened by pests, disease, and/or other stresses, a tree owner or manager may need to decide what risk level he or she is willing to accept and what modifications may be needed. Experienced arborists can aid in this decision process by conducting a professional risk assessment that specifies the likelihood of whole or partial tree failure, the consequences of such a failure, and the potential targets affected. A variety of risk assessment methods have been developed to guide professionals through the tree inspection process. In North America, three risk assessment methods have gained the greatest acceptance among tree care professionals, municipal urban forestry programs, and government agencies. This 8-page fact sheet was written by Andrew K. Koeser, Gitta Hasing, Drew McLean, and Rob Northrop, and published by the UF Department of Environmental Horticulture, November 2013.